The Effect of Adding Sucrose on Product Characteristics in Probiotic Fermented Drinks from “Loka Pere” Banana - Alwi, Achmad Nur Syawal; Trinoviyani, Trinoviyani; Sudirman, Sudirman (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The monosaccharide and fiber content in “loka pere” bananas can be a good growth substrate for probiotic bacteria during the fermentation process in making “loka pere” banana probiotic fermented drinks. The probiotics used can increase the functionality of the product in providing health effects, especially on digestive tract health. The resulting probiotic fermented drink has a distinctive sour taste; usually, sweeteners are added as a flavour balancer in the product so that it can be well accepted by consumers. This study examined the effect of adding variations in sweeteners, namely sucrose, on product characteristics after the fermentation process. Results of the study, it was found that the addition of variations in sucrose of 0%, 3%, 6% did not have a significant effect on the characteristics of pH values (3.97, 3.88, 3.89), total acid (0.70%, 0.77%, 0.70%) and the number of probiotic bacteria (7.53 Log CFU/mL, 7.47 Log CFU/mL, 7.52 Log CFU/mL) in the product. Therefore, sucrose can be used as a sweetener in making the probiotic fermented banana drink “loka pere” because it does not change other characteristics other than the resulting sweet taste.